2017
DOI: 10.1021/acs.jafc.7b02826
|View full text |Cite
|
Sign up to set email alerts
|

Development of a MALDI–TOF MS-Based Protein Fingerprint Database of Common Food Fish Allowing Fast and Reliable Identification of Fraud and Substitution

Abstract: Fish substitution and fish fraud are widely observed in the global food market. To detect and prevent substitution, DNA-based methods do not always meet the demand of being time- and cost-efficient; therefore, methodology improvements are needed. The use of species-specific protein patterns, as determined by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry, has recently improved species identification of prokaryotes both time- and cost-wise. We used the method to establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 49 publications
0
31
0
1
Order By: Relevance
“…Contrariwise, this pattern is also affected by exogenous natural or anthropogenic factors and thereof is an image of the environment of the biological commodity. Thus, the proteome can be used for tackling the biological origin (like the genotyping) and also to get insights for the determination of the geographical origin , of the cultivation , the production, or of storage processes .…”
Section: Methodsmentioning
confidence: 99%
“…Contrariwise, this pattern is also affected by exogenous natural or anthropogenic factors and thereof is an image of the environment of the biological commodity. Thus, the proteome can be used for tackling the biological origin (like the genotyping) and also to get insights for the determination of the geographical origin , of the cultivation , the production, or of storage processes .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, this study demonstrated the possibility of distinguishing between different catch methods within a species, an aspect of fish fraud which is well known but has never been previously reported [38]. Ever in 2017, a protein fingerprint database of common food fish obtained by application of MALDI-TOF MS was developed [40]. The database contained protein patterns of common food fish prone to substitution.…”
Section: Chemical Methodsmentioning
confidence: 73%
“…The database contained protein patterns of common food fish prone to substitution. Indeed, the substitution rate of fish is often dependent on the species and particular species are subjected to more substitutions compared to other species [40]. Ever in recent times, the application of MALDI TOF MS was adopted to evaluate the efficiency of various protocols for fish species identification [41].…”
Section: Chemical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The database currently comprises 54 fish species. Aspects such as the sensitivity of identification on the species level and the impact of bacterial contamination of fish filets are assessed …”
Section: Fishmentioning
confidence: 99%